Development of an evaluation instrument for career guidance programs using the goal attainment framework - Oktaviana, Dian; Purwoko, Budi; Naqiyah, Najlatun; Winingsih, Evi; Prahani, Binar Kurnia (Multidisciplinary Reviews, 2026)
Career guidance programmes play an important role in preparing students for the world of work, especially in vocational education. This study aims to develop and test the feasibility of instruments that include validity and reliability of career guidance programme evaluation instruments using the framework Goal Attainment Scaling (GAS). The research method used is Research and Development (R&D), which involves the stages of needs analysis, instrument development, validation by experts, field trials, and instrument revision. The instruments developed included the GAS Scale, Interview and Focus Group Discussion (FGD), Activity Observation, and Participant Satisfaction Questionnaire. Validity Content Validity Index (CVI), significant Scale-CVI/Average (S-CVI/Ave) values in each instrument between 0.90-1 and Scale-CVI/Universal Agreement (S-CVI/UA) with values of 0.80-1. was analysed using the feasibility of the instrument is also supported in the trial results. The validity of the 0.580 - 0.808 and the range of reliability values of the entire instrument is 0.727-0.870instrument shows. The results showed that the instrument is relevant for evaluating the effectiveness of career guidance programmes. However, some revisions were made to improve clarity and applicability in the context of vocational education, including refinement of terminology as well as adjustments to industry needs. The implications of this study include strengthening outcome-based evaluation in vocational education as well as providing counsellors with a more objective measurement tool. Further recommendations include testing the instrument in various other vocational education contexts to ensure generalization of the results.